Morphological Characteristics and Taxonomical Positions of Annonaceae in Indonesia - Hamidah, Hamidah; Ayu Lestari, Dewi; Tri Wibowo, Anjar; Suhargo, Listijani; Felayati, Themas; Novitasari, Yeyen (Jurnal Riset Biologi dan Aplikasinya, 2024)
Annonaceae is one of the most important and economically valuable plant families in Malesia region. Taxonomical studies could contribute to further utilization and conservation of the studied taxa. Due to their importance, an update in the morphological characters and taxanomical position of Annonaceae is required. This study aims to characterize the taxonomical position and relationships of 24 species belongs to the family Annonaceae found in the Purwodadi Botanic Gardens. In this work, we reported the taxonomical position and the phenetic clustering of 24 Annonaceae species collected from the Purwodadi Botanic Garden, East Java, Indonesia. The taxonomical study was performed based on morphological and phenetic approach where 81 characters (leaves, stem, and flower) were used in the analysis. A dendogram was produced following the scoring of the character using statistical program PAST ver. 3.0. (Hierarchial Cluster Analysis using Jukes Cantor Similarity approach). The  dendogram showed clear separation between members of sub-family Annonoideae and Malmeoideae; however Alphonsea javanica and Sageraea lanceolata were not grouped into their respective tribe or sub-family. Further studies are required to evaluate these taxonomical separations. Overall, from the 24 studied species, we found that they grouped into 2 sub-family (Annonoideae and Malmeoideae), 3 tribes (Annoneae, Miliuseae, and Uvarieae), and 13 genus (Alphonsea, Annona, Desmos, Fissistigma, Miliusa, Mitrephora, Orophea, Polyalthia, Popowia, Pseuduvaria, Sageraea, Stelechocarpus, dan Uvaria).